Photocatalytic oxidation of oxalic acid in dilute aqueous solution, in a fully illuminated fluidized bed reactor - Pozzo, Roberto Luis (2010)
A comprehensive kinetic model for the photooxidation of oxalic acid (C2O4H4) in a fluidized bed (FB) of a TiO2/quartz sand composite, in a UV-fully illuminated photoreactor, was developed and correlated with experimental results. A proper solution for the mass balance of the reacting system was achieved by combining the complete radiation field profile and the most recent and updated pathway for the adsorption and photodecomposition of oxalic acid onto TiO2 (Mendive et al., 2007), which was employed to determine the kinetic expression and model parameters.